2015
DOI: 10.1186/s13071-015-1202-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of loop-mediated isothermal amplification (LAMP) for simple detection of Leishmania infection

Abstract: BackgroundLeishmaniasis is a neglected tropical disease that is caused by an obligate intracellular protozoan of the genus Leishmania. Recently, an increasing number of autochthonous leishmaniasis cases caused by L. martiniquensis and the novel species L. siamensis have been described in Thailand, rendering an accurate diagnosis of this disease critical. However, only a few laboratories are capable of diagnosing leishmaniasis in Thailand. To expand leishmaniasis diagnostic capabilities, we developed a simple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 47 publications
4
60
0
1
Order By: Relevance
“…Serological tests, however show substantial variations in their sensitivity in different geographical areas (Verani et al, 2009), and display sub-optimal performances (Sanchez-Camargo et al, 2014). Unfortunately, and despite being widely used in different parasitic diseases (Mondal et al, 2016; Sriworarat et al, 2015), PCR-based methods applicable in PoC settings such as those based on simple colorimetric loop-mediated isothermal amplification or Recombinase Polymerase Amplification (RPA) techniques are not yet available for T. cruzi detection.…”
Section: Diagnostic Applications For Chagas D Isease: Pending Issuesmentioning
confidence: 99%
“…Serological tests, however show substantial variations in their sensitivity in different geographical areas (Verani et al, 2009), and display sub-optimal performances (Sanchez-Camargo et al, 2014). Unfortunately, and despite being widely used in different parasitic diseases (Mondal et al, 2016; Sriworarat et al, 2015), PCR-based methods applicable in PoC settings such as those based on simple colorimetric loop-mediated isothermal amplification or Recombinase Polymerase Amplification (RPA) techniques are not yet available for T. cruzi detection.…”
Section: Diagnostic Applications For Chagas D Isease: Pending Issuesmentioning
confidence: 99%
“…Although, a few studies employing LAMP assay to diagnose Leishmania infection are known [2632] however, these assays are limited in their utility because of the false positivity due to cross contamination [29], or prolonged reaction time [31] or the use specialized equipment [32]. Here, we have developed a LAMP assay based on kinetoplast minicircle DNA (kDNA) of L.donovani for reliable and rapid diagnosis of Leishmania infection in a closed tube manner using SYBR Green I for detection of the amplified product.…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, Notomi and collaborators designed LAMP, which is characterized as an isothermic technique with a fast reaction time and high sensitivity that offers several alternatives for the visualization of results including turbidity, fluorescence, and/or color changes. [8][9][10][12][13][14] In 2016, Mondal et al 54 reported the use of a recombinant polymerase amplification assay for the detection of Leishmania donovani; this technique offers a shorter reaction time compared with LAMP. Despite advances in the development of new diagnostic techniques, studies often only report certain aspects relating to the sensitivity and specificity of these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…10 Some studies have demonstrated the use of LAMP against extracts from macerated sandflies 8,11 and several alternatives exist for the visualization of the results including turbidity, fluorescence, and/or color changes. [8][9][10][12][13][14] To date, LAMP has been used for the diagnosis of bacterial, 15 fungal, 16,17 and viral 18,19 infections, as well as parasitic infections such as those caused by Trypanosoma brucei, 20 Plasmodium falciparum, 21 and Trypanosoma cruzi. 22 For the diagnosis of leishmaniasis, LAMP has been used with the implementation of primers targeting the small ribosomal subunit (18S rRNA gene), 10,11,23 kinetoplast DNA (kDNA) for the detection of Old World Leishmania species, [24][25][26] and the Internal Transcribed Spacer 1 (ITS-1).…”
Section: Introductionmentioning
confidence: 99%